Learning to schedule web page updates using genetic programming - Aécio Solano Rodrigues Santos (2013)
One of the main challenges endured when designing a scheduling policy regarding freshness is to estimate the likelihood of a previously crawled web page being modified on the web, so that the scheduler can use this estimation to determine the order in which those pages should be visited. A good estimation of which pages have more chance of being modified allows the system to reduce the overall cost of monitoring its crawled web pages for keeping updated versions. In this work we present a novel approach that uses machine learning to generate score functions that produce accurate rankings of pages regarding their probability of being modified on the Web when compared to their previously crawled versions. We propose a flexible framework that uses Genetic Programming to evolve score functions to estimate the likelihood that a web page has been modified. We present a thorough experimental evaluation of the benefits of using the framework over five state-of-the-art baselines. Considering the Change Ratio metric, the values produced by our best evolved function show an improvement from 0.52 to 0.71 on average over the baselines.